HEMOSUCCUS PANCREATICUS - Sheety, Safal; Shenoy, Sundeep; Costello, Robert; Adeel, Muhammad Yasir; Arora, Ashish (Journal of Ayub Medical College Abbottabad, 2019)
Hemosuccus pancreaticus (HP) defined as bleeding into the pancreatic duct was first described in 1931 by Lower and Farell. HP also popularly known as wirsungorrhaghia and pseudohemobilia is a rare cause of gastrointestinal bleed. The unfamiliarity of this condition makes HP a diagnostic challenge. HP should be considered in patients with chronic pancreatitis presenting with acute gastrointestinal bleeding. The diagnosis is usually confirmed with a computerized tomography (CT) scan of the abdomen. A mesenteric angiogram with coil embolization can be performed to arrest the bleeding. The literature on this condition is restricted to case reports, case series and retrospective studies. We describe a case of HP in a patient with gastrointestinal bleeding and take this opportunity to review the literature outlining the diagnosis and management of HP. Keywords: Hemosuccus pancreaticus; gastrointestinal bleeding; pancreatitis; pseudoaneurysm